2015
DOI: 10.1007/s12033-015-9864-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of a Loop at C-Terminal Domain on the Conformational Stability and Catalytic Efficiency of Chondroitinase ABC I

Abstract: We used a combination of protein engineering and spectroscopic methods to investigate the effect of a long length loop on the conformational stability and activity of chondroitinase ABC I. This study involves manipulation of interactions around Asp(689) as a key residue in the central region of the loop containing residues 681-695 located at C-terminal domain of the enzyme. According to the equilibrium unfolding experiments and considering thermodynamic m value and ΔG(H2O), we found that the folded state of H7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
7
1
Order By: Relevance
“…This is supported by the high K m (or low substrate affinity) of ChABC-55-SH3 compared to the other enzymes. A similar effect was observed by Shirdel et al (29), where structurally stabilized ChABC mutants demonstrated a lower enzymatic efficiency; this was attributed to decreased flexibility of the protein since substrate binding typically results in a conformational change. Notably, increasing the number of mutations did not necessarily lead to decreased function.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is supported by the high K m (or low substrate affinity) of ChABC-55-SH3 compared to the other enzymes. A similar effect was observed by Shirdel et al (29), where structurally stabilized ChABC mutants demonstrated a lower enzymatic efficiency; this was attributed to decreased flexibility of the protein since substrate binding typically results in a conformational change. Notably, increasing the number of mutations did not necessarily lead to decreased function.…”
Section: Discussionsupporting
confidence: 77%
“…Stabilization via mutagenesis often leads to decreased catalytic efficiency (k cat /K m ). For example, H700N/L701T, the most stabilizing mutation to date (29), has an aggregation temperature 16°C greater than wild-type ChABC but is 40% less catalytically efficient. In contrast, ChABC-37-SH3 has an aggregation temperature 6°C greater than wild type, is more active overall, and is only 25% less catalytically efficient for CS degradation.…”
Section: Chondroitin Sulfate a Dermatan Sulfatementioning
confidence: 99%
“…Upon construction of mutants their structural properties and biochemical features were evaluated and discussed. In spite of our previous study [10] both mutants of current research are stabilized in comparison with wild type (WT) protein.…”
Section: Introductioncontrasting
confidence: 67%
“…In this study, two single mutants (L679S, L679D) were constructed. Expression and Purification of WT and mutant proteins were carried out as previously described and protein concentration was determined by the Bradford method .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation